A compreensão de recursos multissemióticos no gênero charge por turmas do 8º ano do ensino fundamental. - Dantas, Francisco Danilo Costa (2024)
This research, of a qualitative nature, aims to contribute to the teaching and learning of multisemiotic resources and to the development of language skills (DOLZ AND SCHNEUWLY, 2004), through reading activities of the cartoon genre in Portuguese language classes at the 8th year of elementary school. The aim is, therefore, to expand the knowledge of students in the 8th year of elementary school through reflective and contextualized activities focused on the cartoon genre. In order to complete this intention, an activity book will be presented (divided into 4 modules) that guide teachers and students, based on the theoretical framework of sociodiscursive interactionism - ISD (BRONCKART, 1999), focusing on the production context. In addition, it will also make use of the collaborations of the grammar of visual design – GDV (KRESS AND VAN LEUWEEN, 1996) in order to assist and improve the understanding of multisemiotic texts. It is important to mention that this work aims to encourage, through the educational device, interactionist classes, proficient reading (and consequently, expansion of knowledge of the world), the criticality of students as active citizens in society. The need for educational activities (reading, speaking and writing, also with a view to semiotic analysis) that aim to improve students' argumentative skills for the full development of interaction in the social environment will also be taken into consideration. AMOSSY (2017; 2020), will be another theoretical contribution, as the author discusses argumentation, pointing out a situation in which those involved act on each other within an interaction.